STUDI PENERAPAN METODE ANALISIS DERIVATIF PADA DATA POTENSIAL GRAVITASI - Muhammad Amir Zain; Muhammad Fahrur Rozi; Anisa Nur Septikasari; Muhammad Nuruddianto; Supriyanto Supriyanto; Ahmad Zarkasyi (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2015)
In geothermal exploration, geophysics method is one of main method which is used to detect the existence geothermal system. The existence of geothermal system can be known with searching earth subsurface structure. Our research goal is to identify subsurface structure that can be used to know geothermal system belong. The method that we used is gravity method. Gravity method is method based on gravity acceleration variation on earh surface. This method can detect subsurface geology structure such as fault, basin, graben, and caldera. To imaging subsurface structure geology more clearly, the result of gavity processing will be processed more advance with derivative analysis method. One of derivative metode that is often used, is horizontal gradient method and second order vertical method. Both of them can know vertical contact between subsurface body and know what kind of fault structure. The final result is anomaly horizontal gradient contour map and anomaly secong ordel vertical gradient map. And than both of map will be analyzed and integrated with gelogical data in field research. Keywords: Gravity, stucture, gradient, fault.